CANCER MUCOSA ANTIGENS A NOVEL PARADIGM IN CANCER IMMUNOTHERAPEUTICS - Snook, Adam E (Bioforum Eur, 2009)
Employing antigens with expression restricted to normal intestinal mucosa and derivative colorectal tumors – cancer mucosa antigens (CMAs) – represents a novel paradigm in anti-tumor immunotherapy. Immune compartmentalization limits tolerance to CMAs and restricts mucosa-targeted autoimmunity, allowing safe and effective immunotherapy for metastatic colorectal cancer. Guanylyl cyclase C (GCC), an intestine/colorectal cancer-restricted protein, is poised for clinical evaluation as the index CMA.